Release of nutrient Elements from Decomposing leeaf Litter of Eucalyptus globulus - Upadhyay, R. K. (Indian Forester, 1982)
Changes in level of Inorganic nutrients. Percentage of organic carbon and fungal population during leaf litter decomposition of Eucalyptus globulus Labill. Were studied. Diffiercnt nutrients were found to exhibit variation in their successive release during various stages of decomposition depending upon the nature of the decomposing substrate, rate of decomposition, mobility of the nutrients, and type and extent of activity of microfungi involved.